2013
DOI: 10.1007/s10689-013-9608-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutation screening in a Norwegian cohort with pheochromocytoma

Abstract: Pheochromocytomas (PHEOs) are neuroendocrine tumours, originating from chromaffin cells in the adrenal medulla. They are either sporadic or hereditary. It is important to identify the hereditary cases, so that patients and relatives with germline mutations can be offered regular surveillance. The objective of this study was the detection of pathogenic germline mutations in a cohort of Norwegian PHEO patients. Blood samples and/or formalin-fixed, paraffin-embedded tissue specimens, were collected from 60 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…8,10,11,58,59 Loss of SDHB protein expression is seen in pheochromocytomas/paragangliomas either harboring a mutation in any of the SDH genes or with somatic hypermethylation of the SDHC promoter region, 42 whereas loss of both SDHB and SDHA immunoreactivity is demonstrated only in the context of an SDHA mutation. [8][9][10][11][12][13][14][15][16][17][18][19][20] In agreement with previous studies, 8,10,11,[17][18][19][20] SDHB-/C-/D-and SDHAmutated tumors displayed the aforementioned and NF1 mutations, 8,10 respectively. By using a mouse monoclonal (21A11) SDHB antibody at a low concentration (1 in 1000), Gill et al 10 suggested that VHL-associated tumors could be classified as negative or weak diffuse rather than positive as demonstrated by a high concentration approach of two SDHB antibodies.…”
Section: Discussionsupporting
confidence: 91%
“…8,10,11,58,59 Loss of SDHB protein expression is seen in pheochromocytomas/paragangliomas either harboring a mutation in any of the SDH genes or with somatic hypermethylation of the SDHC promoter region, 42 whereas loss of both SDHB and SDHA immunoreactivity is demonstrated only in the context of an SDHA mutation. [8][9][10][11][12][13][14][15][16][17][18][19][20] In agreement with previous studies, 8,10,11,[17][18][19][20] SDHB-/C-/D-and SDHAmutated tumors displayed the aforementioned and NF1 mutations, 8,10 respectively. By using a mouse monoclonal (21A11) SDHB antibody at a low concentration (1 in 1000), Gill et al 10 suggested that VHL-associated tumors could be classified as negative or weak diffuse rather than positive as demonstrated by a high concentration approach of two SDHB antibodies.…”
Section: Discussionsupporting
confidence: 91%
“…51,52 Another one was in SDHC (c.380A>G; p.His127Arg), and the last three were in SDHD (c.14G>A; p.Trp5*, c.149A>G; p.His50Arg, and c.274G>T; p.Asp92Tyr). 46,[53][54][55] Among these SDHD mutations, one resulted in a stop codon (p.Trp5*), which cannot be managed by the prediction tools we used but can be considered to Review be damaging because the mutation results in a severely truncated protein. This nonsense variant was identified in a patient suffering from Carney-Stratakis syndrome, with the PGL showing positive SDHB on IHC and the GIST presenting with a negative SDHB on IHC, potentially indicating two different second hit events in the SDHD gene.…”
Section: Genotype-phenotype Correlation Analysismentioning
confidence: 99%
“…has not routinely been analyzed before autumn 2016. The method has been described by Sjursen et al (240).…”
Section: Genetic Analysismentioning
confidence: 99%